Social forces and aging - Atchley, Robert C. (Wadsworth/Thomson Learning, 2004)
Atchley and Barusch's interdisciplinary approach has produced a text that provides the concepts, information, insight, and examples students need to achieve a basic understanding of aging as a social process. Covering the physical problems, inner experiences, and instrumental needs of the aging, the text examines aging on both an individual and societal level. It covers major areas of theory, research, social policy, and practice in a clear and organized manner to make social gerontology accessible to students from all backgrounds. This text is the classic book for the course that continually keeps pace with the dramatic changes in the field, including new theories, research, programs, and issues. Atchley and Barusch first examine individual aging-and adaptation to aging in everyday life, then move on to explore the needs and demands that aging, as a phenomenon, presents to society, while also delving into society's response to aging